New data on the genus Eustrangalis Bates from China (Coleoptera: Cerambycidae, Lepturinae) - Wang, Yingqi; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2024)
In the present paper, a new species, Eustrangalis (Eustrangalis) fuscisuturalis sp. nov. is described and illustrated, Eustrangalis (Metalleustrangalis) aeneipennis aeneipennis (Fairmaire, 1889) is newly recorded from Hubei, China. The syntype photographs of Eustrangalis (Eustrangalis) distenioides Bates, 1884 and holotype photographs of Eustrangalis (Eustrangalis) latericollis Wang & Chiang, 1994 are presented. Photographs of the living adults of E. (Metalleustrangalis) aeneipennis aeneipennis (Fairmaire, 1889) and E. (Eustrangalis) fuscisuturalis sp. nov. are also given.